USING THE CONCEPT OF PUBLIC-PRIVATE PARTNERSHIP TO MODEL THE PROCESS OF LOCAL ECONOMIC DEVELOPMENT - Komarovskyi , I. (Theory and Practice of Public Administration, 2021)
The synthesis of the known definitions of LED in the literature makes it possible to conclude that the concept of local development is always based on initiatives coming from the bodies of public administration, representatives of business and the public representatives. Consideration of the LED in terms of possible approaches to its implementation allows us to conclude on the feasibility of using the concept of PPP. Such a partnership can significantly increase the efficiency and potential of the public sector without the addition of additional resources from the executive authorities. But the proposal to rely on the strategy of the LED concept PPP puts on the agenda the task of developing and optimizing the appropriate management model. The purpose of the article is to determine the mechanisms of public administration of LEDs and to substantiate the areas of optimization of partnership projects according to the criterion of their compliance with the conditions of sustainable development. In the research to propose the possible form of organization (model) of the PPP project in terms of its resource provision and the participation of public and private partners at each stage of the LED. In order to determine the conditions for the effectiveness of partnerships in the LED projects, it is suggested that graphing methods be used. It is proved that the maximum possible economic efficiency of LED on the basis of the concept of PPP can be obtained under the conditions of the intersection of the curves “Project effectiveness” and “Efficiency of budget funds”. The intersection determines the ratio “Moderate budget support = Optimal cost-effectiveness.” It is clear that if the PPP concept will be on the basis of the LED, that issue of profit for the private sector is more important than the social component. Therefore, the essence of the application of the concept of PPP in LED programs is how to determine the relationship between business and the local community, the conditions for their interaction with public administration bodies.